Prediction of effector proteins and their implications in pathogenicity of phytopathogenic filamentous fungi: A review - Wu, Y.; Xie, L.; Jiang, Y.; Li, T.
Plant pathogenic fungi encode and secrete effector proteins to promote pathogenesis. In recent years, the important role of effector proteins in fungi and plant host interactions has become increasingly prominent. In this review, the functional characterization and molecular mechanisms by which fungal effector proteins modulate biological processes and suppress the defense of plant hosts are discussed, with an emphasis on cell localization during fungal infection. This paper also provides a comprehensive review of bioinformatic and experimental methods that are currently available for the identification of fungal effector proteins. We additionally summarize the secretion pathways and the methods for verifying the presence effector proteins in plant host cells. For future research, comparative genomic studies of different pathogens with varying life cycles will allow comprehensive and systematic identification of effector proteins. Additionally, functional analysis of effector protein interactions with a wider range of hosts (especially non-model crops)will provide more detailed repertoires of fungal effectors. Identifying effector proteins and verifying their functions will improve our understanding of their role in causing disease and in turn guide future strategies for combatting fungal infections.
Keywords: EFFECTOR PROTEINS; FUNGI; PLANT-FUNGI INTERACTION; VIRULENCE; PLANT DISEASE